Efeitos tóxicos do Cádmio e o papel protetor do Hidrolisado da clara na toxicidade induzida pelo metal - (:unkn) unknown (Universidade Federal do Pampa, 2020)
Cadmium (Cd) is a heavy, non-essential metal, widely used in industry and found in air, food, contaminated water, and cigarettes. Exposure to Cd can damage the cardiovascular, nervous, endocrine, and reproductive systems. The mechanisms involved in these effects are related to increased oxidative stress, apoptosis, DNA damage, and inflammation. The investigation of functional ingredients such as egg white hydrolysate (EWH) with antioxidant and anti-inflammatory properties protects against the effects of metals. Investigate the effects of exposure to high concentrations of Cd in the cardiovascular and reproductive systems and test the effectiveness of EWH to protect this other system from the damage induced by exposure to metal in rats. In the cardiovascular system: male Wistar rats (3 months, ± 300 g) were treated for 14 days and divided into: a) Control - Ct (distilled water), b) Cadmium - Cd (Cadmium chloride - CdCl2 - 1mg / kg, intraperitoneal - ip) and to analyze the possible protective effect of EWH on the reproductive system, the following groups were added: c) EWH (1 g / kg/ day, gavage), and CdEWH (CdCl2 + EWH). Were analyzed: systolic blood pressure (SBP) by caudal plethysmography; vascular reactivity in resistance mesenteric arteries (MRA) and aorta in an organ bath system; the level of reactive oxygen species (ROS), lipid peroxidation, total antioxidant capacity in the aorta and MRA, and the activity of the angiotensin-converting enzyme (ACE) in plasma by biochemical assays; in situ production of superoxide anion by dihydroethidium (DHE) and the presence of prostanoids (COX-2) by immunofluorescence. In the reproductive system it was analyzed: concentration of Cd by an inductively coupled mass spectrometer (ICP-MS); sperm quality (sperm motility, daily sperm production, number of sperm and transit time in the epididymis, sperm membrane integrity) and biochemical assays of ROS levels, lipid peroxidation, total antioxidant capacity, GSH level and activity of catalase, glutathione peroxidase and superoxide dismutase enzymes in testis and epididymis. The results are expressed as mean and SEM, compared by Student's t-test for vascular data and are expressed as median [minimum - maximum] (Kruskal - Wallis test) or mean ± SEM (ANOVA), p <0.05 considered significant (CEUA UNIPAMPA: 13/2019). Cd- induced: I) increase in SBP (Ct: 117.6 ± 2.5; Cd: 147.9 ± 5.4* mmHg); II) increased vasoconstrictor response in MRA and aorta, reduced endothelial modulation, reduced nitric oxide bioavailability in MRA, increased participation of NADPH oxidase-derived ROS, increased COX-2 and increased renin-angiotensin system in the contractile response; III) increased ACE activity and ROS production, especially superoxide anion, with greater detection of the NADPH oxidase (NOX-1 subunit), AT1 and COX-2 receptors. Co-treatment with EWH prevented in the reproductive system: I) increased deposition of Cd in the testis (μgCd / g/ tissue - Ct: 0.04 ± 0.02; Cd: 4.68 ± 1.03* ; EWH:0.01 ± 0.0; CdEWH: 1.85 ± 0.25#); II) the reduction of sperm motility; III) damage to the sperm membrane; IV) reduction in daily sperm production; V) the increase in sperm transit time in epididymis; VI) damage to morphology; VII) the increase in oxidative stress in the testis and epididymis; VIII) the reduction of the GSH level and restored the GPx activity. Exposure to Cd in high concentrations induces arterial hypertension, increases vascular reactivity, and worsens relaxation due to the increase in reactive oxygen species, greater activation of the renin-angiotensin system, and activation of the inflammatory process. This metal also significantly affects the functions of the reproductive system, impairing motility, morphology and sperm viability with damage to target organs due to increased oxidative stress, increasing the risk of infertility. Therapeutic strategies such as dietary supplementation with EWH can serve as protection against the toxic damage induced by this metal.
Cadmium toxic effects and the protective role of egg white hydrolyzate in metal-induced toxicity
Keywords: Cadmium; Toxicity; Hypertension; Vascular reactivity; Reactive species; Inflammation; Reproductive system; Sperm quality; Egg white hydrolysate (EWH); Antioxidant; Functional food; Cádmio; Toxicidade; Hipertensão; Reatividade vascular; Antioxidante; Espécies reativas; Espécies reativas qualidade espermática; Alimento funcional; CNPQ::CIENCIAS BIOLOGICAS